Detection of Phytochemicals and Antioxidant Activity in the Leaf Extracts of Aegle marmelos L. Correa (Rutaceae) - Anusha B.K; Sowmya, T.N.; Monnanda Somaiah Nalini (Research Perspectives of Microbiology and Biotechnology Vol. 8, 2024)
Aegle marmelos L. Corr., popularly known as ‘bael’ is an important medicinal plant used in ayurvedic preparations. In this study, the phytochemical constituents and antioxidant activity of extracts from the leaves of A. marmelos were investigated by the standard methods. The mature leaves were collected during the month of February 2022. The sample was shade-dried, powdered and extracted with hexane, methanol and water according to the standard procedure. The extracts were subjected to preliminary phytochemical tests, and tested for the total phenolic content by Folin-Ciocalteau (FC) method and radical scavenging activities by 1,1-diphenyl-2-picryl hydrazyl (DPPH) method. The methanolic leaf extract was subjected to Thin Layer Chromatography (TLC) for the detection of phenolic and terpenoid compounds. Phytochemical tests revealed the presence of terpenoids, steroids, cardiac glycosides and alkaloids among the three solvent extracts. The phenolic content of the extracts was estimated with Gallic acid as standard. The aqueous and methanol extract of leaves recorded a high total phenolic content of 298.27µg GAE/g and 299.35 µg GAE/g. High radical scavenging activity was detected in the aqueous extract (IC50= 40.95 µg/mL). Further, the methanolic leaf extract was subjected to Thin Layer Chromatography (TLC) for the detection of phenolic and terpenoid compounds with the spraying reagents which showed the presence of several bands with Rf values.